Physical fitness of women over 50 years of age and self-esteem quality of life and health - Tomczak Mariusz; Ignasiak Zofia; Sławińska Teresa (Sciendo, 2019)
Study aim: The aim of this study was to examine whether in women over 50 years of age the rate of decline in physical fitness with age affects the self-assessment of health and quality of life.